Association between thermal comfort and cortisol depends on the air temperature and exposure time. (1st April 2023) - Zhang, Xiaoxia; Hu, Songtao; Guo, Chengji; Liu, Rujin; Tong, Li; Shi, Baoshan; Li, Bin
Abstract: Exploring the link between thermal comfort and cortisol, a stress hormone, at different air temperatures can give a theoretical basis for creating a comfortable and healthy indoor environment, although the relationship is not yet obvious. We considered three temperatures and two exposure levels, collected the subjects' subjective evaluations and saliva, detected the concentration of cortisol in saliva, and analyzed the change characteristics of subjective evaluations and cortisol concentration at different temperatures with exposure time and their relationships at different exposure times. Subjective evaluations were better and cortisol concentration was lower at neutral temperature, according to our findings. Furthermore, there was a U-shaped distribution of cortisol concentration with thermal sensation vote (TSV), and cortisol concentration decreased with increasing thermal comfort vote (TCV). In comparison to "hot" and "cold, " the concentration of cortisol corresponding to "neutral" after 30 min of exposure declined by 179.0% and 59.3%, respectively; the concentration for "very uncomfortable" was higher by 191.4% than for "comfortable." Following a 60-min exposure, the concentrations that corresponded to "neutral" and "very uncomfortable" were, respectively, lower by 89.3% and 143.0% than "hot" and "comfortable." Our findings suggest that cortisol derived from human saliva may be a novel and useful objective indicator assessing human thermal comfort. This study can deepen our understanding of the relationship between human thermal comfort and stress hormones, and relevant conclusions provide theoretical basis for building indoor thermal environment. Highlights: Air temperature significantly affected the human salivary cortisol concentration. The more comfortable the environment, the lower the cortisol concentration. Exposure time affected the relations between cortisol concentration and TSV and TCV. Salivary cortisol may be a new and useful index assessing human thermal comfort.